Iowa Birdline update, October 10, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for October 10, 1994. Highlights of the update include details on the later passerine migration, including sightings of Yellow-rumped Warblers and White-throated Sparrows. Also of note was the observation of thirteen species of Sparrows in central Iowa and a report from a hawk watch held at Grammer Grove Park, including sightings of 26 Swainson's Hawks and 55 Red-tailed Hawks. Also included are handwritten notes for the next week's update with sightings of an Ibis and a Red-necked Grebe. Epson - sheet feed/flatbed